1999
DOI: 10.1111/j.1469-7793.1999.0815n.x
|View full text |Cite
|
Sign up to set email alerts
|

High intracellular [Ca2+] alters sarcoplasmic reticulum function in skinned skeletal muscle fibres of the rat

Abstract: 1. The effect on sarcoplasmic reticulum (SR) function of exposure to high intracellular [Ca¥] was studied in mechanically skinned fibres from the extensor digitorum longus muscle of the rat, using caffeine to assay the SR Ca¥ content. 2. A 15 s exposure to 50 ìÒ Ca¥ irreversibly reduced the ability of the SR to loadÏretain Ca¥ and completely abolished depolarization-induced Ca¥ release, whereas a 90 s exposure to 10 ìÒ Ca¥ had no detectable effect on either function. The reduction in net SR Ca¥ uptake: (a) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 31 publications
1
43
1
Order By: Relevance
“…The amount of slippage/leakage of SERCA pumps increases with increasing temperature (16) and ADP concentration (38). Compared with the skinned fiber study by Lamb and Cellini (35), both the experimental temperature (23 vs. 30°C) and the ADP concentration in the fibers (ϳ0.1 vs. ϳ10 M) were higher in the present study. Higher coupling ratios have been reported for rabbit skeletal muscle preparations, and, in contrast to our calculations, the Ca 2ϩ -to-ATP ratio was higher in slow-twitch muscle SR vesicles (i.e., 0.98 Ca 2ϩ /1 ATP) than in fast-twitch skeletal muscle SR vesicles (i.e., 0.37 Ca 2ϩ /1 ATP) (44).…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…The amount of slippage/leakage of SERCA pumps increases with increasing temperature (16) and ADP concentration (38). Compared with the skinned fiber study by Lamb and Cellini (35), both the experimental temperature (23 vs. 30°C) and the ADP concentration in the fibers (ϳ0.1 vs. ϳ10 M) were higher in the present study. Higher coupling ratios have been reported for rabbit skeletal muscle preparations, and, in contrast to our calculations, the Ca 2ϩ -to-ATP ratio was higher in slow-twitch muscle SR vesicles (i.e., 0.98 Ca 2ϩ /1 ATP) than in fast-twitch skeletal muscle SR vesicles (i.e., 0.37 Ca 2ϩ /1 ATP) (44).…”
Section: Discussioncontrasting
confidence: 74%
“…However, our values for ATP turnover by SERCAs strongly suggest that the Ca 2ϩ -to-ATP coupling ratio is actually much lower than 2:1 under physiological conditions. If the coupling ratio was 2 Ca 2ϩ to 1 ATP, the rate of Ca 2ϩ uptake (which is equal to the rate of SR Ca 2ϩ leakage in resting muscle) would be ϳ318 nmol·g Ϫ1 ·s Ϫ1 in EDL and ϳ418 nmol·g Ϫ1 ·s Ϫ1 in soleus, which is ϳ22-to 26-fold higher than what has been measured in mechanically skinned EDL and soleus fibers from the rat (35,38,39). Taking into account the ATP turnover rates that we measured in this study and the SR Ca 2ϩ leak rate reported by Lamb and Cellini (35) for rat EDL (which would be equal in soleus), we can calculate coupling ratios of ϳ0.09 Ca 2ϩ /1 ATP in EDL and ϳ0.07 Ca 2ϩ /1 ATP in soleus.…”
Section: Discussionmentioning
confidence: 73%
“…Furthermore, the higher activity of Ca 2+ -activated potassium channels in mdx than control mice is clear functional evidence in favour of a basal subsarcolemmal increase of Ca 2+ [31]. Some authors have suggested that exposure of fibres to high [Ca 2+ ] reduces the ability of the sarcoplasmic reticulum to load and retain Ca 2+ [26]. This sarcoplasmic reticulum Ca 2+ efflux mechanism is not well understood and could occur by reversal of the Ca 2+ -ATPase, via a distinct channel or through the ryanodine receptor/Ca 2+ -release channels [15,41].…”
Section: Discussionmentioning
confidence: 96%
“…This decline in function, referred to as fatigue, has a complex etiology which can involve various factors, e.g., reduced availability of energy, build-up of metabolites, and dysfunction of excitation-contraction coupling (for review see Fitts 1994). Although suggested already in 1976 by Eberstein and Sandow, alterations in the function of the sarcoplasmic reticulum (SR), which regulates the intracellular Ca 2+ concentration, have only recently been considered, as a major contributor to fatigue (Lamb and Cellini 1999).…”
Section: Introductionmentioning
confidence: 99%